PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT TERPADU (LEMPERMADU) BERBASIS MASJID DALAM PENGEMBANGAN USAHA PETERNAKAN SAPI RAKYAT DI NUSA TENGGARA BARAT - Mashur (SANGKAREANG, 2017)
Institutional breeder is an umbrella organization for farmers to perform activities of agribusiness farms, from upstream to downstream, establish coordination with relevant stakeholders. Institutional role of farmers is very important and strategic in order to realize the relationship between farmers in the cooperative network with stakeholders to build and strengthen institutions, in order to encourage the growth of agribusiness farms more efficient, effective and sustainable. Each institutional breeders have the opportunity to shape and develop institutions breeders, however, institutional breeders should be formed based on the need to develop business activities. After institutional breeders formed, it is necessary to facilitate the form of assistance by the department/agency responsible for the function of the farm districts/cities, provinces and the center so that institutions can be run professionally and able to develop itself into an institution breeder independent, as well as improving its business as business entities commercial. To that end, the necessary facilities for economic institutional breeders, among others: (1) Strengthening the institutional capacity of business managerial economics breeders; (2). The development of networks and partnerships; (3). Development of information services, apprenticeships and training for prospective breeders economic institutions. The objective is to convey the idea of thinking of alternative models of institutional empowerment of cattle farms of the people in an integrated manner by optimizing the function of the mosque for the prosperity of the people, through economic empowerment for the community, especially the livestock farmers in the cattle business people who constitute the bulk of the cattle farmers in NTB partially great is mukiminmosque. Thus, this model is expected to be developed in order to reduce poverty, especially in rural areas.